Reliability Analysis of Diesel Engine at LNG Plant using Counting Process - Darmanto, Seno; Atmanto, Ireng Sigit; Permana, Bagus Hendra (Vocational College of Universitas Diponegoro, 2019)
The purpose of this research is to analyze the reliability of diesel engine as driver for fire water pump. To determine the reliability level of the diesel engine, this research will apply counting process so that the rate of failure of the diesel engine can be known. The data used as basis for calculation is failure data gained from maintenance work order databases from 2012 to 2017. The data obtained will be processed using counting process method to produce mathematical modeling to predict the amount of failure to diesel engines in the future. From 4 diesel engines, only 3 parametric failure rate (l) that could be generated, for 33-GE-5A, for 33-GE-5B, and for 33-GE-5C, since 33-GE-5D was severely damaged in September 2015. The mathematical modeling will be verified using the Pearson's Chi-squared Test method to ensure the validity of the mathematical model can be guaranteed. The result of the goodness of fit test shows that only parametric failure rate (l) for 33-GE-5B and 33-GE-5C that could be accepted. The outcome mathematical model will be used to predict future behavior and failure of the unit so effective and efficient maintenance strategy for 33-GE-5B and 33-GE-5C could be applied